A novel function of CXCL10 in mediating monocyte production of proinflammatory cytokines. Issue 5 (1st November 2017) - Zhao, Qihong; Kim, Taeg; Pang, Jian; Sun, Wendy; Yang, Xiaoxia; Wang, Jinhong; Song, Yunling; Zhang, Hongwei; Sun, Huadong; Rangan, Vangipuram; Deshpande, Shrikant; Tang, Huaping; et al.
Abstract : CXCL10 plays a novel, important role in mediating proinflammatory cytokine production by innate cells, and contributes to the mucosal inflammation and tissue injury in colitis. Abstract : IFN‐γ–inducible protein 10 (CXCL10), a chemokine that is abundantly secreted in response to inflammatory stimuli, has been implicated in the pathogenesis of multiple inflammatory diseases, such as inflammatory bowel disease. Whereas CXCL10 is traditionally recognized for recruiting pathogenic T cells to inflamed sites, its nonchemotactic role during inflammation remains poorly defined. In this report, we identified a novel function of CXCL10 in the regulation of the inflammatory potential of human monocytes to produce cytokines. We found that CXCL10 was necessary and sufficient for IFN‐γ–primed human monocytes to induce a robust production of proinflammatory cytokines, such as IL‐12 and IL‐23. CXCL10‐induced monocyte production of these cytokines depended on CXCR3 receptor engagement as well as on the Iκ B kinase and p38 MAPK signaling pathways. By using an innate‐mediated murine colitis model, we demonstrated that anti‐CXCL10 Ab treatment robustly suppressed the local production of myeloid‐derived inflammatory cytokines and intestinal tissue damage. Together, our data unravel a previously unappreciated role of CXCL10 in the amplification of myeloid cell–mediated inflammatory responses. Targeting CXCL10 is therefore an attractive approach to treating inflammatory diseases that are driven by innate and adaptive immunity.